The ironies of the new religious liberty litigation - Kaveny, Cathleen (Daedalus)
The plaintiffs in recent religious liberty litigation are very different from plaintiffs in earlier cases. They are not marginalized or politically powerless. They seek to return the country to its conservative roots, rather than to escape the dominant liberal mindset. But their success has come at a cost to their own deep commitments. This essay will proceed as follows. First, I describe key elements of recent religious liberty cases, highlighting the ways in which they go beyond the older case law that ostensibly served as precedent. Second, I argue that these decisions ironically fall prey to the communitarian critiques of modern liberal democracy that have been prominent in conservative religious circles for thirty years or more. Finally, I sketch a new way forward, drawing on the notion of civic friendship and the Golden Rule, and suggest the question religious believers should be asking now is not (3z(BWhat are our legal rights?(3y (Bbut (3z(BWhat do we owe morally to fellow citizens who believe differently than we do?(3y (B- Reproduced s
Keywords: Religious liberty